Pillar 3: market discipline of the key stakeholders in CEE commercial bank and turbulent times - Munk, Michal; Pilkova, Anna; Benko, Lubomir; Blažeková, Petra (Journal of Business Economics and Management, 2017)
The study presented in the paper contributes to covering the gap in the area of sufficient information disclosure that also increases the interests of relevant stakeholders in contributing to depository market discipline and in being relevant to their interest within Pillar 3 framework. This paper is focused on an analysis of website data dedicated to Pillar 3 disclosures of commercial banks and on studying the behaviour of stakeholders in relation to the timing of serious market turbulence. The examined data consists of log files that were pre-processed using web mining techniques and from which were extracted frequent itemsets by quarters and evaluated in terms of quantity. The authors have proposed a methodology to evaluate frequent itemsets of web parts over a dedicated time period. The results show that stakeholders’ interest in disclosures is lower after turbulent times in 2009, higher in the first quarter, also higher together with annual reports (lower for Pillar 3 solo information). The paper’s results suggest that further changes in commercial banks´ information disclosure are inevitable in order to achieve an effective market discipline mechanism and meaningful disclosures according to the regulator´s expectations.